Reimagining ancient household ethos? - Mouton, Elna (Neotestamentica, 2014)
The article explores the dynamic of New Testament households and their codes of conduct. It focuses on the reconfigured husband/wife relationship in the household code of Ephesians 5:21-6:9 in view of the code's ambivalent relation to the rest of the letter as well as its complex history of interpretation. Since Christianity's foundational documents originated from (and are often read) within patriarchal societies, influenced by the hierarchical ethos of empire, a major challenge is whether and how a text such as the Ephesians code provides a lens through which it may be reimagined today - even against its patriarchal grain and history of interpretation. In view of feminist and postcolonial criticism, it is argued that the code serves as an ongoing invitation to resist any form of exploitative power in contemporary as well as ancient empire.